Roll Your Own - Anthes, Gary H (Computerworld, 2004)
Accommodating the special needs of users is just one reason why companies continue to develop their own applications. IT shops are bucking the trend toward off-the-shelf applications and are opting to use custom-developed systems in the following situations: * A package falls short in one or two crucial respects and is bloated with unneeded features. * Companies can develop their own system more cheaply, especially when they have deep subject-matter expertise. * An application is of strategic importance, and the company wants to control every aspect of it. Cardinal Health Inc. developed its own SFA tools - Web-based applications written in Visual Basic. Because the company had a long history of working with these kinds of tools, it knew exactly what it wanted and saw in-house development as low-risk and low-cost. In addition, says Rich Gius, CIO in Medical Products and Services, ongoing maintenance and support costs for a commercial product would have been far greater. IT executives generally say it makes little sense to develop your own commodity, or utility, system, such as payroll or general ledger. But one company's utility can be another's strategic asset. Choice Homes Inc., a $750 million house-builder in Arlington, Texas, chose to develop its own suite of accounting systems - general ledger, accounts payable and accounts receivable - even though many mature commercial choices are available. It was the only way to get the extremely flexible reporting necessary to satisfy the needs of autonomous, remote construction managers.